Problems of the Wife's Role as a Housewife and Full-Time Worker in Forming a Maslahah Family - Sho'ib, Fahri Nur (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
This study discusses the problematic dual role of wives as housewives and full-time workers in fostering a virtuous family, with a case study at PT Sumber Makmur Anugrah, Temanggung. This phenomenon is increasingly relevant in the modern era, when women are free to work and pursue careers outside the home, but are still burdened with domestic responsibilities. The approach used is qualitative with a case study method and in-depth interviews with wives who have been married for more than five years and work full-time. The results of the study indicate that this dual role causes various problems, including decreased communication between husband and wife, degradation of harmony (mahabbah), reduced provision of exclusive breastfeeding, and weak supervision of children. However, some informants still try to balance domestic and professional roles in order to realize a virtuous family, namely a harmonious family, spiritually and socially qualified, and useful in the community. This study recommends the importance of husband and wife cooperation and family-friendly company policies to optimally support the dual role of wives. [Penelitian ini membahas problematika peran ganda istri sebagai ibu rumah tangga sekaligus pekerja fulltime dalam membina keluarga maslahah, dengan studi kasus di PT Sumber Makmur Anugrah, Temanggung. Fenomena ini semakin relevan di era modern, ketika perempuan memperoleh kebebasan untuk bekerja dan berkarier di luar rumah, namun tetap dibebani tanggung jawab domestik. Pendekatan yang digunakan adalah kualitatif dengan metode studi kasus dan wawancara mendalam terhadap istri-istri yang telah menikah lebih dari lima tahun dan bekerja fulltime. Hasil penelitian menunjukkan bahwa peran ganda ini menimbulkan berbagai persoalan, antara lain menurunnya komunikasi suami istri, degradasi keharmonisan (mahabbah), berkurangnya pemberian ASI eksklusif, serta lemahnya pengawasan terhadap anak. Meski demikian, sebagian informan tetap berupaya menyeimbangkan peran domestik dan profesional demi mewujudkan keluarga maslahah, yaitu keluarga yang harmonis, berkualitas secara spiritual dan sosial, serta bermanfaat di lingkungan masyarakat. Penelitian ini merekomendasikan pentingnya kerja sama suami istri dan kebijakan perusahaan yang ramah keluarga guna mendukung peran ganda istri secara optimal.]